Pengaruh Sistem Informasi Akuntansi dan Kinerja Pegawai Terhadap Kualitas Laporan Keuangan (Studi Kasus Pada Dinas Tenaga Kerja Kabupaten Mandailing Natal) - Rizky Putri Mahfuz; Zulia Hanum (Politeknik Ganesha Medan, 2023)
This study aims to examine the effect of accounting information systems and employee performance on the quality of financial reports at the Mandailing Natal District Manpower Office. The method used in this study is an associative approach using primary data in the form of respondents' answers to questionnaires distributed directly to 41 employees of the Mandailing Natal Regency Manpower Office. Then, the data analysis method used is SEM – PLS using SmartPLS 4.0 software. The results of this study explain that the accounting information system has no significant effect on the quality of financial reports, but employee performance has a significant effect on the quality of financial reports at the Mandailing Natal District Manpower Office.